Narkomania: drugs, HIV, and citizenship in Ukraine - Carroll, Jennifer J. (Cornell University Press, 2019)
"Narkomania is an ethnography of addiction treatment in Ukraine, which describes how people who use drugs became pawns in Ukraine's 2014 revolution and the ongoing civil war"--